Postoperative Calcium Management in Same‐Day Discharge Thyroid and Parathyroid Surgery. (1st March 2016) - Nelson, Kurt L.; Hinson, Andrew M.; Lawson, Bradley R.; Middleton, Derek; Bodenner, Donald L.; Stack, Brendan C.
Abstract : Objective: To describe a safe and effective postoperative prophylactic calcium regimen for same‐day discharge thyroid and parathyroid surgery. Study Design: Case series with chart review. Setting: Tertiary referral academic institution. Subjects and Methods: In total, 162 adult patients who underwent total thyroidectomy, completion thyroidectomy, unilateral parathyroidectomy, parathyroidectomy with bilateral neck exploration, or revision parathyroidectomy were identified preoperatively to be candidates for same‐day discharge. All patients in this study were successfully discharged the same day on our standard prophylactic calcium regimen. Results: Less than 1% (1/162) of patients re‐presented to the hospital within 30 days of surgery, and that patient was successfully discharged from the emergency department after negative workup for hypocalcemia. There was no significant difference between preoperative and postoperative calcium levels in the total/completion thyroidectomy groups (9.3 vs 9.2 mg/dL, respectively; P =. 14). The average postoperative calcium level in the parathyroid group was well within normal limits (9.5 mg/dL), and the difference in postoperative calcium levels between revision and primary parathyroidectomy cases was not significantly different ( P =. 34). Conclusion: The reported calcium regimen demonstrates a safe, effective, and objective means of postoperative calcium management in outpatient thyroid and parathyroid surgery in appropriately selected patients.